2002
DOI: 10.1053/jhep.2002.32668
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between acetaldehyde levels and cell survival in ethanol-metabolizing hepatoma cells

Abstract: T he vast majority of ingested ethanol is oxidized to acetaldehyde by the hepatocytes of the liver. 1,2 It is thought that the metabolism of ethanol by hepatocytes is the reason that the liver is a target for the detrimental effects of chronic alcohol abuse. 3 Ethanol oxidation by hepatocytes results in many metabolic changes, some of which have been shown to be detrimental to cells. It has been proposed that chronic ethanol abuse promotes continual hepatocyte destruction that, in turn, stimulates abnormal hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 30 publications
8
91
0
2
Order By: Relevance
“…In the case of Rab7, the GTP‐loaded and active form of this protein exhibits a strong affinity for the RILP, an effector that promotes the recruitment of dynein–dynactin complexes to lysosomes for subsequent transport and fusion 22, 34. Accordingly, a GST‐tagged form of RILP was used in a pulldown assay to measure total Rab7 activity in EtOH‐metabolizing VA‐13 cells, a widely used HepG2 hepatoma‐derived cell line that stably expresses alcohol dehydrogenase 26, 35. An EtOH exposure of 24 hours led to a dramatic decrease in the activity of Rab7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Rab7, the GTP‐loaded and active form of this protein exhibits a strong affinity for the RILP, an effector that promotes the recruitment of dynein–dynactin complexes to lysosomes for subsequent transport and fusion 22, 34. Accordingly, a GST‐tagged form of RILP was used in a pulldown assay to measure total Rab7 activity in EtOH‐metabolizing VA‐13 cells, a widely used HepG2 hepatoma‐derived cell line that stably expresses alcohol dehydrogenase 26, 35. An EtOH exposure of 24 hours led to a dramatic decrease in the activity of Rab7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All protocols were approved by the Institutional Animal Care and Use Committee at the VA Nebraska‐Western Iowa Health Care System Research Service. Adh1‐expressing VA‐13 hepatocytes26 were kindly provided by Terrence Donohue (University of Nebraska Medical Center) and cultured in Dulbecco's modified Eagle's medium containing 400 µg/mL zeocin. Glutathione S ‐transferase (GST)–Rab‐interacting lysosomal protein (RILP) was a gift from C. Bucci (University of Salente, Lecce, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol or acetaldehyde, which is a carcinogen, 24 affects cell proliferation and induces DNA damage, which may lead to malignant changes. 25,26 Furthermore, accumulating evidence suggests that prostate carcinogenesis by alcohol is mediated through increased estrogens and decreased androgens and sex hormone-biding globulin. [27][28][29][30][31][32] Results regarding the effect of smoking on prostate cancer have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaldehyde is a well-recognized toxin producing singlestrand DNA breaks 7 and protein adducts. 8 While not previously described as a therapeutic agent, the ability of prolonged acetaldehyde exposure to damage or inhibit cell growth in vitro [9][10][11] and in vivo is well characterized. 12 The physiological metabolism of alcohol takes place primarily within the liver where ethanol is converted to acetaldehyde, mainly via the action of alcohol dehydrogenase.…”
mentioning
confidence: 99%
“…Parallel results have been reported for the human colorectal cell line Caco-2 with a 150% increase in cell doubling time following exposure to 500 mM acetaldehyde for 3 days. 16 More recent studies using plasmid-mediated transfer of ADH genes into cells with low ALDH activity have demonstrated that intracellular production of acetaldehyde reaching concentrations of up to 600 mM can result in growth inhibition 10,17,18 and induction of apoptosis. 10,19 To investigate the potential of intracellular acetaldehyde generation as a therapeutic approach, we have used the human beta 2 ADH enzyme.…”
mentioning
confidence: 99%